2022
DOI: 10.15376/biores.17.2.1988-2002
|View full text |Cite
|
Sign up to set email alerts
|

Firewater toxicity after extinguishing natural-based insulation materials

Abstract: Water is the most widely used fire extinguishing agent. It is used to eliminate a wide range of fires, often occurring in ecologically sensitive areas. There is little information on the toxicity of the fire-fighting substances in connection with aquatic and terrestrial organisms. Toxic substances often present in fire waters slow down life processes. As a result, some organisms die. This study deals with the extinguishing of burning solids (fiberboard, cannabis, straw, cork) with extinguishing water and asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Hybska, H. and co-authors dealt with the examination of the toxic effects of the firewater in detail and concluded that if environmental contamination can no longer be prevented, the spread of contaminated firewater must at least be reduced [41]. Vanessa, C. Erazo-Chamorro, et al, in their article, assess the information about security risk factors and necessary safety requirements for a safe workplace [42].…”
Section: In the Field Of Fpp Policies And Safety Measuresmentioning
confidence: 99%
“…Hybska, H. and co-authors dealt with the examination of the toxic effects of the firewater in detail and concluded that if environmental contamination can no longer be prevented, the spread of contaminated firewater must at least be reduced [41]. Vanessa, C. Erazo-Chamorro, et al, in their article, assess the information about security risk factors and necessary safety requirements for a safe workplace [42].…”
Section: In the Field Of Fpp Policies And Safety Measuresmentioning
confidence: 99%
“…4,5 The previous literature reported that addition of soluble chemical additives (surfactant and phosphorus-nitrogen active salts) could remarkably improve the re-ghting performance, owing to the improved wetting, penetrating, and active free radical quenching ability surrounded the surface fuels. 6,7 Nevertheless, such extinguishing agents cannot form a compact carbonaceous protective layer on the solid fuel substrates, which limits their re suppression efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that it is a material that does not resist heat must be considered (Preventing fires in baled hay and straw 2012; Štulajter et al 2015;Čekovská et al 2017;Marková et al 2018b;SDSU Extension 2020). The impact of burning and fire suppression on aquatic and terrestrial environments also requires attention (Veľková et al 2019;Hybská et al 2020Hybská et al , 2022.…”
Section: Introductionmentioning
confidence: 99%